Developing primary student innovators through local wisdom and integrated learning - Suwicha Wansudon; Trai Unyapoti; Phatcharida Inthama (Institute of Advanced Engineering and Science, 2026)
Elementary science, technology, engineering, arts, and mathematics (STEAM) education often struggles with abstract, disconnected lessons, leading to students engaging in “making without learning”. Addressing this gap, this study evaluated a novel STEAM learning package that uniquely integrates regional local wisdom with educational board games to enhance the innovator competencies and STEAM process knowledge of fifth-grade students. Employing a rigorous pretest-posttest quasi-experimental design, the study involved 240 students across four diverse school jurisdictions in Bangkok. To address common methodological limitations in educational research, a linear mixed model (LMM) was utilized to isolate the intervention’s true effect from nested school contexts. The results demonstrated that the experimental group achieved significantly higher innovator competencies and STEAM knowledge compared to the control group. Crucially, the variance analysis revealed that school administrative structure and resources had a negligible impact on student outcomes. This underscores the study’s strongest novelty: combining cultural heritage with gamification not only provides a highly effective pedagogical scaffold but also serves as an equitable instructional tool, successfully bridging the gap between abstract science and meaningful application across diverse educational environments.